The mediating effects of job satisfaction on leadership style and organisational commitment in tourism villages in Indonesia - Nadia, Zulfa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The purpose of this study is to examine the mediating effects of job satisfaction on leadership style and organizational commitment in tourism villages in Indonesia. It focuses on leadership styles in three tourism village organizations in Indonesia: the Poncokusumo tourism village, the Ngadas tourism village and the Gubugklakah tourism village; and how these leadership styles influence job satisfaction and organizational commitment in terms of its implementation. A quantitative research design and a cross-sectional survey are used to test the hypotheses of the study, while the descriptive and inferential statistics are applied to answer research questions and to test the hypotheses. The sample population of the study consists of the managerial staff, guides and homestay employees from the aforementioned tourism villages in Indonesia. A total of 152 (99 employees of homestay and 53 employees of the main crew) are drawn from a stratified sample randomly. The measurement of transformational, transactional, and passive-avoidant/laissez-faire leadership style items are adapted from the full-range MLQ-5X Short by Bass and Avolio (1997; 2000) while the job satisfaction measurement is adapted from the measurement by Spector (1994). Lastly, to measure organisational commitment, items are adapted from the revised organisational subscale created by Meyer, Allen, and Smith (1993). The findings of the study show that there is a relationship between the transformational leadership style and organisational commitment. There is also a positive significant relationship between the transformational leadership style and job satisfaction. Implications of this study are to managers especially those in tourism villages in terms of being more effective, understanding the employees and being able to create a workplace that avoids internal organizational culturally-based conflict. Thus, through comprehending how the employees think, managers are able to motivate them, assign them jobs and control interactions within the organization. These findings, therefore, can be studied and practised by the other tourism villages.